1976
DOI: 10.1111/j.1600-0536.1976.tb03029.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergic contact response to vitamin A acid

Abstract: Three patients treated daily with vitamin A acid cream experienced after one week, seven weeks and 14 weeks respectively sudden redness and itching at the treated sites. Patch testing with the cream (containing 0.05% vitamin A acid) and with vitamin A acid 0.05% in absolute alcohol produced strongly positive reactions in the patients but only slight erythema in some of the controls. Since patch testing with vitamin A acid 0.005% in absolute alcohol elicited no response in controls but positive reactions in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1978
1978
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Tomb and colleagues describe a single case of contact allergy to tretinoin in a 34‐year‐old man, and patch testing was positive to tretinoin and isotretinoin . Earlier case reports of allergic contact dermatitis to retinoic acid have also been described . To our knowledge, there have been no reported cases of allergic contact dermatitis after the ocular use of retinoic acid.…”
Section: Case and Discussionmentioning
confidence: 80%
“…Tomb and colleagues describe a single case of contact allergy to tretinoin in a 34‐year‐old man, and patch testing was positive to tretinoin and isotretinoin . Earlier case reports of allergic contact dermatitis to retinoic acid have also been described . To our knowledge, there have been no reported cases of allergic contact dermatitis after the ocular use of retinoic acid.…”
Section: Case and Discussionmentioning
confidence: 80%
“…The dermatitis was undoubtedly provoked by retinoic acid, whereas the positive patch tests with both preparations may have been partly irritant. Although five controls were negative to both prepara-tions, other authors have found that a 0.05 % concentration of retinoic acid caused slight erythema in some controls (Lindgren et al 1976). Allergic contact dermatitis (ACD) to a.-methylene-y-butyrolactone derivatives (Fig.…”
mentioning
confidence: 86%
“…During this period, she presented with intermittent erythema three times, but it always disappeared within 48 h without any other manifestation. Sensitization to retinoic acid has been described several times (Nordqvist & Mehr 1975, Jordan et al 1975, Lindgren et al 1976). In Poland this preparation has been only recently introduced and applied to a small number of patients.…”
mentioning
confidence: 99%
“…Efficacy of tretinoin used as short contact therapy is superimposable on that of tretinoin used according to standard modality [2,3]. Things to be followed for prevention of RD are: to begin the treatment with lower concentrations of retinoid, when possible; to begin the treatment applying the retinoid daily for a few hours and slowly increasing the application time until skin tolerance is acquired (hardening or accommodation phenomenon) [5] [6] published the first two cases of ACD caused by all-trans-retinoic acid, less than 20 cases have been published [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Most of the cases were caused by tretinoin (TABLE 2) [6-10, 12,13,[15][16][17][18][19]21].…”
Section: Retinoidsmentioning
confidence: 98%